Veterinary drugs - a responsibility of veterinarians - Abdullah, Abdul Salam (Persatuan Doktor Veterinar Malaysia, 1986)
Veterinarians, with excellent background in the biological sciences are best suited to undertake not only public health responsibilities, but also play an important role in handling of drugs and food production. They are responsible in the development and supply of drugs, health care and welfare of animals through rational use of safe drugs as well as ensuring hygienic conditions to slaughter the animals. It is also their responsibility to detect drug residues in animal products and to reassure consumers on the wholesomeness of animal products they consume.